Desenvolvimento e avaliação biológica de novos derivados 2-amino tiofênicos indólicos como possíveis agentes anti-leishmania - Félix, Mayara Barbalho (2016)
Leishmaniasis is a group of diseases caused by protozoa of the genus Leishmania, transmitted by insects phlebotomines. The recommended treatments for leishmaniasis are very toxic and unsatisfactory. Therefore, it is urgent to find new anti-Leishmania drugs that are more effective against the parasite and exhibit low toxicity to the host. Thus, this study sought to synthesize, characterize and evaluate the anti-Leishmania potential novel 2- amino-thiophenes. Thirty-two 2-amino thiophenes indole derivatives were studied by our research group. The synthesis of compounds showed a yield ranging from 31.7% (TN7-6) to 96.4% (TN6-4). In addition, the fusion ranged between of 150 ° C (TN5) and 295ºC (TN6-4). All compounds showed antipromastigota activity obtained with different IC50 values, ranging from the 2.07 - 1067 μg/ml. None of tiofenicos indole derivatives showed cytotoxicity to erythrocytes of human origin, compared to the referenced drugs. Among compounds with anti-Leishmania activity, TN8-7 substance was selected to proceed with the studies due to its high selectivity index (SI> 193.2). It was observed that L. amazonensis strains resistant to trivalent antimony continued with the same levels of sensitivity to TN8-7 presented by crops sensitive to antimony. Additionally, it was observed that the anti-Leishmania TN8-7 activity is associated with DNA fragmentation of promastigotes of the parasite. Therefore, the results of this study suggest that indole 2-amino thiophenes derivatives are promising molecules and possible drug candidates for the therapy of leishmaniasis.